Corrosion Behavior of Cr19Fe22Co21Ni25Mo13 Alloy in 1M Nitric Acid and 1M Hydrochloric Acid Solutions - Chun-Huei Tsau (MDPI AG, 2021)
The present work studied the microstructures of Cr19Fe22Co21Ni25Mo13 alloy, and tested the polarization properties in deaerated 1M nitric acid and 1M hydrochloric solutions at different temperatures. The alloy was processed by an argon atmosphere arc-melting. Results indicated that the microstructure of Cr19Fe22Co21Ni25Mo13 alloy was a dendritic one. The dendrites of Cr19Fe22Co21Ni25Mo13 alloy were an FCC structure, and the interdendrites of Cr19Fe22Co21Ni25Mo13 alloy were a eutectic structure with two phases of FCC and simple cubic (SC). The Cr19Fe22Co21Ni25Mo13 alloy had better corrosion resistance compared with commercial 304 stainless steel in both deaerated 1M HNO3 and 1M HCl solutions. The corrosion types of Cr19Fe22Co21Ni25Mo13 alloy in both of 1M HNO3 and 1M HCl solutions were uniform corrosion.